2013
DOI: 10.1042/bj20121541
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies of FosB: a divalent-metal-dependent bacillithiol-S-transferase that mediates fosfomycin resistance in Staphylococcus aureus

Abstract: FosB is a divalent-metal-dependent thiol-S-transferase implicated in fosfomycin resistance among many pathogenic Gram-positive bacteria. In the present paper, we describe detailed kinetic studies of FosB from Staphylococcus aureus (SaFosB) that confirm that bacillithiol (BSH) is its preferred physiological thiol substrate. SaFosB is the first to be characterized among a new class of enzyme (bacillithiol-S-transferases), which, unlike glutathione transferases, are distributed among many low-G + C Gram-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
105
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(117 citation statements)
references
References 43 publications
8
105
2
2
Order By: Relevance
“…In previous studies, FosB was shown to mediate fosfomycin resistance in S. aureus through the use of BSH to disrupt the epoxide ring of fosfomycin (18,19,38). We investigated here the role of BSH in fosfomycin resistance mediated by FosB in a wide variety of methicillin-sensitive and methicillin-resistant S. aureus strains, including clinical isolates.…”
Section: Fosb Utilizes Bsh As a Substrate To Confer Fosfomycin Resistmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, FosB was shown to mediate fosfomycin resistance in S. aureus through the use of BSH to disrupt the epoxide ring of fosfomycin (18,19,38). We investigated here the role of BSH in fosfomycin resistance mediated by FosB in a wide variety of methicillin-sensitive and methicillin-resistant S. aureus strains, including clinical isolates.…”
Section: Fosb Utilizes Bsh As a Substrate To Confer Fosfomycin Resistmentioning
confidence: 99%
“…Intracellular reduced thiols (BSH, Cys, and coenzyme A [CoA] sulfhydrate [CoASH]) were derivatized, in triplicate, with monobromobimane (mBBr). Samples for disulfide analysis were first treated with Nethylmaleimide (NEM), followed by dithiothreitol (DTT) reduction and labeling with mBBr of reduced thiols and oxidized disulfides (BSSB and cystine), and were analyzed by fluorescent high-pressure liquid chromatography (HPLC), as previously described (18,25). However, it is not possible to accurately quantify CoA disulfide because the DTT treatment used in the disulfide analysis also cleaves thioesters such as acetyl-CoA into CoA, resulting in an overestimate of CoA disulfide (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms for fosfomycin resistance are encoded on plasmids and the chromosome. Resistance to fosfomycin is conferred by the production of the plasmid-encoded enzymes FosA, FosB, FosC, and FosX, which leads to inactivation of fosfomycin (13)(14)(15)(16). Chromosomal mutations that lead to the expression of MurA variants that have impaired fosfomycin binding or result in overexpression of MurA also confer resistance to fosfomycin.…”
mentioning
confidence: 99%
“…Note that fosfomycin resistance provides a semiquantitative measure of in vivo BSH levels since resistance is largely dependent on the BSH-dependent thiol-transferase FosB. Since the K m of FosB for BSH is in the millimolar range (higher than in vivo levels during growth; Roberts et al, 2013), FosB activity, and therefore fosfomycin resistance, is very sensitive to even small changes in BSH levels (Gaballa et al, 2010;Parsonage et al, 2010). Since pMUTIN disruptants are generally polar on downstream genes (Fig.…”
Section: The Bshc Gene Is Part Of a Complex Operonmentioning
confidence: 99%